2016
DOI: 10.20471/acc.2016.55.02.14
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Promotion of Nursing

Abstract: SUMMARY -Nurses have great infl uence on health care system. As they face many diff erent states of aff airs nowadays, it is necessary to fi nd a way to promote and enable their profession. Th e signifi cant interaction between nurses and patients and other medical professions makes them a powerful marketing tool of a medical institution. Th erefore, the promotion of their image is necessary because of authorizing their professional status. Th ere are numerous ways of creating and improving their image. Some o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Stereotypes attribute to nurses such as physician's assistant, lack of social life, "angel" and prostitute figures are closely related to the profession's history (3) . Factors that contribute to the maintenance of these stereotypes include female condition, presence of hierarchy between physicians and nurses, misrepresentation in the media, and lack of marketing by nurses (3,8) . The mistaken assumption that nursing has no scientific knowledge, the hands-on feature attributed to care and lack of knowledge of the different degrees of nursing staff training and their fields of activity also contribute to nurses' image devaluation (3,7) .…”
Section: Introductionmentioning
confidence: 99%
“…Stereotypes attribute to nurses such as physician's assistant, lack of social life, "angel" and prostitute figures are closely related to the profession's history (3) . Factors that contribute to the maintenance of these stereotypes include female condition, presence of hierarchy between physicians and nurses, misrepresentation in the media, and lack of marketing by nurses (3,8) . The mistaken assumption that nursing has no scientific knowledge, the hands-on feature attributed to care and lack of knowledge of the different degrees of nursing staff training and their fields of activity also contribute to nurses' image devaluation (3,7) .…”
Section: Introductionmentioning
confidence: 99%
“…This short web-survey, designed primarily to explore gaps in the knowledge of midwives working in different counties in Croatia, showed that some misconceptions still existed. Having in mind the study group’s grounds in gynecology and obstetrics, and their public health relevance, targeted educational activities both during midwife formal education ( 18 ) and on job ( 19 ) are required to improve the group’s knowledge on emergency contraception. National guidelines on oral emergency contraception issued by the Society of Gynecologic Endocrinology and Human Reproduction (HDGEHR), Croatian Society of Gynecology (HDGO) and Gynecology Primary Practice Section of the Croatian Medical Association ( 20 ) are an available learning tool and the most appropriate local source of information on emergency contraception.…”
Section: Discussionmentioning
confidence: 99%
“…Th e objective of this study was to determine the nutritional status of elderly persons receiving home care after hospital discharge and to identify the factors that aff ect their nutritional status in order to lay the foundation for further development of healthcare and improvements of healthcare in this population, which has been insuffi ciently studied until now. Since visiting nurses were involved in the data gathering process, a questionnaire drawn up on the basis of validated tools (NRS-2002 and DETERMINE checklist) was used to ensure simplicity and ease of use 10 . According to the medical history data obtained, the fi ndings on the prevalence of the most frequent chronic illnesses correspond to other data available in scientifi c publications.…”
Section: Discussionmentioning
confidence: 99%